First Five Year Plan Bombay State Sholapur District - Government of Bombay (Government of Bombay, 1954)
The First Five-Year Plan (1951–56) for Sholapur District presents a comprehensive framework for socio-economic development, focusing on agriculture, education, health, infrastructure, and industrial growth. Agriculture, the backbone of the district’s economy, is targeted through improved irrigation projects, seed distribution, modern farming techniques, and livestock management, particularly emphasizing crops such as Jowar and Bajra. The plan promotes minor irrigation works and veterinary services to enhance productivity and sustainability. Education initiatives include establishing 550 primary schools, expanding secondary education through technical and private schools, and developing vocational training facilities like the Northcote Technical High School, with an emphasis on practical skills in mechanical engineering, carpentry, tailoring, and weaving. Adult education programs and targeted support for backward classes aim to address high illiteracy and promote social equity. Health services are strengthened through medical units and programs combating prevalent diseases like malaria, while welfare measures support housing, cooperative societies, and the economic empowerment of farmers and artisans. Infrastructure improvements, particularly road construction, enhance connectivity between villages, towns, and markets, facilitating trade and access to services. The cooperative movement, including credit societies and industrial cooperatives, underpins economic development, supporting both agriculture and cottage industries. Despite challenges such as limited teacher training facilities and resource constraints, the plan lays a structured foundation for sustainable growth, improved living standards, and long-term community development in Sholapur District.
Sholapur District
Sholapur District
Keywords: State Five Year Plan; Sholapur District; Agricultural Development; Irrigation Projects; Primary Education; Secondary Education; Vocational Training; Health Services; Cooperative Societies; Cottage Industries; Infrastructure Development; Adult Education